(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Dental crown materials can influence the biological response of the surrounding gingival tissues. Nickel–chromium alloys and gold alloys are widely used in fixed prosthodontics due to their mechanical properties and clinical durability. However, differences in corrosion resistance, metal ion release and biocompatibility may affect periodontal health around these restorations. Understanding their clinical impact is essential for selecting appropriate restorative materials. This study aimed to compare the gingival health status around nickel–chromium alloy crowns and gold alloy crowns among adult patients. Methods: This cross-sectional comparative study was conducted at the Department of Prosthodontics, Bangabandhu Sheikh Mujib Medical University in collaboration with Beau-Dent, The Dental Specialist, Dhaka, Bangladesh, from January to December 2019. A total of 60 patients aged 30–40 years with existing full-coverage crowns were included. Participants were categorized into two groups based on crown material: nickel–chromium alloy crowns (n=32) and gold alloy crowns (n=28). Gingival health was assessed using the Gingival Index, Plaque Index, Sulcus Bleeding Index and probing depth measurements. Data were analyzed using SPSS version 25.0. Results: Healthy gingiva was observed in 12.5% of participants with nickel–chromium crowns and 32.1% with gold crowns. Moderate and severe gingivitis were more prevalent in the nickel–chromium group. Poor plaque scores were recorded in 28.1% of the nickel–chromium group compared with 17.8% in the gold group. Similarly, higher levels of bleeding and deeper probing depths were observed around nickel–chromium crowns, although differences were not statistically significant. Conclusion: Gold alloy crowns demonstrated comparatively better gingival health outcomes than nickel–chromium alloy crowns. Material biocompatibility may influence periodontal responses around fixed prostheses. Journal of Paediatric Surgeons of Bangladesh (2023) Vol. 14 (1 & 2): 39-44